Design and development of controlled porosity osmotic tablet of diltiazem hydrochloride - Sadhana R Shahi; Nityanand S Zadbuke; Bhushan Gulecha; Shantanu S Shivanikar; Shivram B Shinde (Wolters Kluwer Medknow Publications, 2012)
The present work aims towards the design and development of extended release formulation of freely water-soluble drug diltiazem hydrochloride (DLTZ) based on osmotic technology by using controlled porosity approach. DLTZ is an ideal candidate for a zero-order drug delivery system because it is freely water-soluble and has a short half-life (2-3 h). Sodium chloride (Osmogen) was added to the core tablet to alter the solubility of DLTZ in an aqueous medium. Cellulose acetate (CA) and sorbitol were used as semipermeable membrane and pore former, respectively. The effect of different formulation variables namely concentration of osmogen in the core tablet, % pore former, % weight gain, pH of the dissolution medium and agitation intensity on the in vitro release was studied. DLTZ release was directly proportional to % pore former and inversely proportional to % weight gain. The optimized formulation (F8) delivered DLTZ independent of pH and agitation intensity for 12 h at the upper level concentration of % pore former (25% w/w) and middle level concentration of % weight gain (6% w/w). The comparative study of elementary osmotic pump (EOP) and controlled porosity osmotic pump revealed that it superior than conventional EOP and also easier and cost effective to formulate.